A closer look into the structure and magnetism of the recently fallen meteorite Ribbeck - Mieszko Kołodziej; Danuta Michalska; Karol Załęski; Igor Iatsunskyi; Andrzej Muszyński; Emerson Coy (Scientific Reports)
Abstract Meteorites are a unique source of geological information about our early Solar System and the difference between planets and asteroids. In this study, meteorite Ribbeck (2024 BX1, SAR 2736) from the recently fallen asteroid (21.01.2024), collected right after the fall, was investigated. This meteorite is classified as a coarse-grained brecciated aubrite. The main mineral phases are enstatite, albite, and forsterite. X-ray structural analysis and Raman Spectroscopy indicate its complex metamorphic history, starting with magmatic crystallization and following metamorphic evolution (e.g., impacting). Energy-dispersive. X-ray spectroscopy (EDS) confirms the presence of unusual minerals such as oldhamite, brezinanite (daubréelite, zolenskyite), wassonite/heideite, and alabandite, that formed under highly reductive conditions, with oxygen fugacity ΔIW (logfO 2 ) in a range of -5 to -7. Similar conditions can be found on the Mercury or the Asteroid 3103 Eger. Magnetic measurements confirm that the primary magnetic components in the meteorite are accessory minerals - sulphides and metallic nodules.